2007
DOI: 10.1021/jf072024w
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Isoflavones and Other Phenolics in the Aerial Parts of Trifolium Species

Abstract: Some species of the genus Trifolium are well-known for their content of isoflavones, which are natural compounds showing health-promoting activities. Until recently, only a few species of this genus have been characterized with respect to their composition. In the present study, 57 Trifolium species have been analyzed for their contents of isoflavones, phenolic acids, flavonoids, and clovamides. The cluster analysis of experimental data allowed us to identify a number of species, which should be of interest as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 12 publications
7
76
1
2
Order By: Relevance
“…Paddock F vegetation had a higher specific contribution of PSM-rich species than T (42-46% vs. 29-27%) because of the abundance of species from the Compositae, Rosaceae, Polygonaceae, and Fabaceae families, all generally rich in either volatiles [38] or polyphenols [23,31]. Paddock T vegetation was dominated by Trifolium alpinum, a species from the Fabaceae family known to be rich in polyphenols [39].…”
Section: Vegetation Composition Foragementioning
confidence: 99%
See 1 more Smart Citation
“…Paddock F vegetation had a higher specific contribution of PSM-rich species than T (42-46% vs. 29-27%) because of the abundance of species from the Compositae, Rosaceae, Polygonaceae, and Fabaceae families, all generally rich in either volatiles [38] or polyphenols [23,31]. Paddock T vegetation was dominated by Trifolium alpinum, a species from the Fabaceae family known to be rich in polyphenols [39].…”
Section: Vegetation Composition Foragementioning
confidence: 99%
“…One pasture was largely dominated by Trifolium alpinum, from a genus rich in polyphenolic compounds [39]. The other pasture was rich both in high-forage quality species (Festuca nigrescens, Phleum alpinum, and Trifolium repens) and in other species, such as Alchemilla xanthochlora and Polygonum bistorta, belonging to families with high PSM content [18,31,38].…”
Section: Introductionmentioning
confidence: 99%
“…The plants were chosen on the basis of results from our previous studies, recommendations of traditional medicine, agricultural significance, and available data on their promising chemical profiles. A general analysis of the phytochemical profiles of 57 Trifolium species, reported by Oleszek et al (2007), indicated T. scabrum as one of the three plants containing the highest amount of isoflavones (7-9% of the dry matter). Concentrations of isoflavones in other species were higher or comparable with the amounts occurring in T. pratense (1-4% of the dry matter), whereas T. pallidum was classified to the cluster of the species rich in clovamides.…”
Section: Introductionmentioning
confidence: 99%
“…The HR-MALDI/TOF mass spectrum of 2 supported a molecular formula of C 41 H 64 O 15 . The ESI-MS mass spectrum in the negative ion mode showed the major ion peak at m/z 795.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 87%